2018
DOI: 10.21833/ijaas.2018.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Nursing student’s knowledge and attitudes toward pain management at Hail University, Saudi Arabia

Abstract: The objective of this study is to examine undergraduate nursing students' knowledge and attitudes toward pain management in the University of Hail and differences between groups defined in terms of socio-demographic and other selected characteristics students in knowledge and attitude with regard pain management scores. The descriptive, cross-sectional design included a sample of 150 undergraduates Saudi nursing students of the University of Hail in the kingdom of Saudi Arabia to investigate the knowledge and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
3
2
3
Order By: Relevance
“…On the contrary, this result is inconsistent with study of Al Khalaileh and Al Qadire (2013) who found that there was no significant statistical difference in the mean of total knowledge and attitude scores between students who received pain education and those who did not [13]. Also, the result of the current study disagreed with Alsaqri (2018) who stated that there was no significant statistical difference found in the students' mean scores in terms of attending a training course on pain management [16].…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…On the contrary, this result is inconsistent with study of Al Khalaileh and Al Qadire (2013) who found that there was no significant statistical difference in the mean of total knowledge and attitude scores between students who received pain education and those who did not [13]. Also, the result of the current study disagreed with Alsaqri (2018) who stated that there was no significant statistical difference found in the students' mean scores in terms of attending a training course on pain management [16].…”
Section: Resultscontrasting
confidence: 99%
“…A total of 191 nursing students completed and returned the mean score for all participants was 20.9 which translates to 52.3%, indicating that the students' knowledge and attitudes were suboptimal [14]. Moreover, the current study agreed with Al-Khawaldeh, et al ( 2013) who said that students demonstrated a poor understanding of pain knowledge and attitudes with a KASRP score of 34.1% (SD = 9.9) [15], and consistent with Alsaqri (2018) who found that nursing students have a lack of knowledge and attitudes towards pain management and the mean correct score for the entire scale was 41.8% (SD = 3.71) [16]. Furthermore, the current study is consistent with the results of Karman, et al ( 2018) who stated that the mean score of the NKASRP was 15.85 ± 3.25% (poor level of pain knowledge and attitude) [17].…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The present study found that around half of the respondents had knowledge that intravenous as route of medication act quicker to relieve pain which is in line with the study conducted in Saudi Arabia. 14 The present study showed nearly three-fourth of the respondents had knowledge as intramuscular analgesics should be avoided for older adult which is inconsistent with the study in Turkey showed less than two-third of the respondents had knowledge that intramuscular analgesics should be avoided for older adult. 13 This might be due to different study setting.…”
Section: Discussioncontrasting
confidence: 99%
“…This erroneous belief is not limited to the current study, as reported in the literature [ 15 , 24 , 31 ]. Pain is a unique subjective experience, so the appropriate attitude of the nurses must be not to disregard the patient’s complaint of pain even if he is smiling, joking, or grimacing [ 3 , 15 , 37 ]. The result of this inappropriate attitude would be disregarding or an underestimation of the patient’s self-report of pain, which affects the pain management [ 21 ].…”
Section: Discussionmentioning
confidence: 99%